WAKTU KONTAK DAN pH OPTIMUM SISA BUANGAN BATU BATA TERAKTIVASI di-(2-ethylhexcyl) phosphate acid (D2EHPA,) SEBAGAI PENJERAP Pb 2+ - Eirene Grace Fransina; Jolantje Latupeirissa; Quendeline Stefanus (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2018)
Determination of optimum pH and contact time, of broken brick from Latuhalat village as adsorbent of Pb2+ through impregnation with di-(2-ethylhexcyl) phosphate acid (D2EHPA) has been done. Bricks impregnated with di-(2-ethylhexcyl) phosphate acid concentration of 700 ppm to enlarge the surface area of ​​adsorption on bricks. The result of analysis using AAS show that optimum contact time is 3 hours, optimum pH is 8, with weight of adsorbent is 0,2 g, adsorbate concentration is 100 ppm and adsorption capacity is 49,9985 mg/g adsorbent.